Role of imaging in the management of thyroglossal duct cyst carcinomas (TGC-TIRADS): a single centre retrospective study over 16 years - Mahajan, Abhishek; Deokar, Shonal; Suryavanshi, Shubham; Agarwal, Ujjwal; Vaish, Richa; Shukla, Shreya; Vaidya, Tanvi; Smriti, Vasundhara; Tuljapurkar, Vidisha; Rastogi, Shivam; Shaikh, Atif; Chaturvedi, Pankaj; et al. (Frontiers in Oncology, 2023)
Thyroglossal duct cyst (TGDC) is the most frequently encountered developmental anomaly in thyroid genesis with a reported incidence of 7% in the adult population [1]. The cyst is known to develop anywhere along the pathway of thyroid descent but is more frequently seen in the infrahyoid neck in the midline. The incidence of malignancy in a TGDC is approximately 1%; a majority of these are papillary carcinomas [1,2]. This is a rare entity and this study was conducted at a single tertiary care centre which spanned over a decade which adds practice changing evidence based knowledge to existing literature on this rare entity. This is one of the largest series where imaging features have been studied. A comprehensive study which conclusively establishes the imaging features predictive of malignancy in TGDC carcinomas (TGDCa), the protocol for optimal management, clinical outcome and long-term survival of these patients is not available. Consequently, providing patients and clinicians with pertinent information with respect to the role of imaging, further investigations, management and prognosis poses a challenge. Although TGDC carcinoma is thought to have an excellent prognosis [3], there is not enough data available on the long-term survival of these patients.The aim of this study was to identify whether neck ultrasound (US) can serve as an accurate imaging tool for the pre-operative diagnosis of TGDC carcinomas. We also analyzed the management protocols utilized and their impact on patient outcomes. To the best of our knowledge, this is the largest study of its kind and the first comprehensive study in patients with TGDC carcinomas, which provides evidence-based information regarding the role of imaging, optimal management protocol and clinical outcomes of these cases.